2018
DOI: 10.1002/jmri.26229
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of uterine artery geometry and hemodynamics in human pregnancy with 4d flow mri and its correlation with doppler ultrasound

Abstract: Background: Uterine artery (UtA) hemodynamics might be used to predict risk of hypertensive pregnancy disorders, including preeclampsia and intrauterine growth restriction. Purpose or Hypothesis: To determine the feasibility of 4D flow MRI in pregnant subjects by characterizing UtA anatomy, computing UtA flow, and comparing UtA velocity, and pulsatility and resistivity indices (PI, RI) with transabdominal Doppler ultrasound (US). Study Type: Prospective cross-sectional study from June 6, 2016, to May 2, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
1
18
1
Order By: Relevance
“…PC‐MRI permits the quantification of the faster (center of the vessel) and slower (vessel wall) velocities within a vessel, and good spatial resolution allows for accurate vessel cross‐sectional area measurements throughout the cardiac cycle. Our measurements of UTA blood flow were considerably higher than those derived using a similar technique, four‐dimensional (4D) flow MRI, which measured bilateral flow of 606 mL/min . The considerably lower UTA blood flow by 4D flow MRI can be attributed to measurements made earlier in pregnancy, at around 26 weeks' gestation, and lower spatial resolution.…”
Section: Discussioncontrasting
confidence: 54%
“…PC‐MRI permits the quantification of the faster (center of the vessel) and slower (vessel wall) velocities within a vessel, and good spatial resolution allows for accurate vessel cross‐sectional area measurements throughout the cardiac cycle. Our measurements of UTA blood flow were considerably higher than those derived using a similar technique, four‐dimensional (4D) flow MRI, which measured bilateral flow of 606 mL/min . The considerably lower UTA blood flow by 4D flow MRI can be attributed to measurements made earlier in pregnancy, at around 26 weeks' gestation, and lower spatial resolution.…”
Section: Discussioncontrasting
confidence: 54%
“…While it is possible that US overestimated mean velocity over the cross‐sectional area by sampling the center of the vessel, we may have underestimated flow rate due to the lower spatial and temporal resolution of a 1.5‐T MRI scanner compared with the 3‐T magnetic field strength used for two‐dimensional phase‐contrast MRI 42 . However, we believe this would have been a systematic bias affecting measurements in both COMP and no‐COMP subjects and we have demonstrated repeatability of these measurements in a previous study 14 . Fortunately, substantial progress in 4D flow MRI is being made to decrease scan time and improve temporal and spatial resolution 43,44 .…”
Section: Discussionmentioning
confidence: 82%
“…A key advantage of 4D flow MRI during pregnancy is its large spatial coverage, which allows evaluation of the entire course of the UtA. We have demonstrated that use of this modality is technically feasible in pregnant women 14 , but did not correlate UtA flow measurements with pregnancy outcome. In this study, therefore, we sought to further validate 4D flow MRI measurement of UtA blood flow by exploring the association with adverse pregnancy outcome and comparing it with Doppler US measurement of UtA blood flow.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“… 121 Flow through the uterine arteries was also measured in human pregnancies, with velocity measurements agreeing with those obtained with Doppler US. 122 A strength of PC-MRI is the ability to assess blood flow in a 3D volume, which could allow assessment of placental and cardiovascular adaptations throughout gestation as a result of fetal programming.…”
Section: Diffusion Perfusion and Flowmentioning
confidence: 99%